Теоретичні аспекти фінансового забезпечення соціального захисту населення - Насібова, Ольга Вікторівна (ТОВ "Редакція журналу "Економіка та держава", 2019)
У статті проаналізовано різноманітні концептуальні підходи до сутнісно-змістовної характеристики поняття "соціальний захист": як функція держави (суспільств); як комплекс (сукупність) дій, заходів, методів, гарантій, прав, інститутів, стратегій, програм; як система; як процес, діяльність; як інститут. Обгрунтовано важливість розуміння соціального захисту населення як системи фінансових відносин необхідної для компенсації соціальних ризиків і забезпечення соціальної безпеки. Визначено основні функції системи соціального захисту населення, які найповніше розкривають сутність досліджуваного поняття, відображаючи його властивість у реальній дійсності та визначаючи роль у системі суспільно-економічних відносин. Акцентується увага на потенційних джерелах створення фондів фінансових ресурсів системи соціального захисту. У процесі дослідження зазначено, що первинні доходи населення відіграють вирішальну роль у формуванні високого рівня життя громадян та соціально-економічного розвитку. Розкрито сутність та особливості фінансового забезпечення соціального захисту населення. Визначено державні і недержавні джерела фінансових ресурсів, а також форми фінансового забезпечення соціального захисту громадян.

The article presents the study of theoretical aspects of financial provision of social protection of the population. Various conceptual approaches to the essence-content characteristic of the concept of "social protection" are analyzed: as a function of the state (societies); as a complex (set of) actions, measures, methods, guarantees, rights, institutes, strategies, programs; as a system; as a process, activity; as an institution. The importance of social protection is objectively determined by the social need in the mechanism of mitigation of socio-economic contradictions in the process of production and distribution of material goods. The dependence of the efficiency and effectiveness of the system of social protection of citizens on the quality of financial security determines the interest of economists in the financial capacity of this system. The importance of understanding social protection of the population as a system of financial relations necessary for compensation of social risks and ensuring social security is substantiated. The basic functions of the system of social protection of the population, which most fully reveal the essence of the concept of "social protection", are defined, reflecting its property in real life and determining the role in the system of socio-economic relations. The focus is on potential sources of financial resources for the social protection system. In the course of the research it is noted that primary incomes of the population play a decisive role in the formation of a high standard of living for citizens and socio-economic development. The existing trends in income levels reflect the needs of citizens in their support through the system of social protection and indicate the degree of effectiveness of public policy in the field of financial regulation of social benefits. The essence and features of financial provision of social protection of the population are revealed. Established state and non-state sources of financial resources, as well as forms of financial provision of social protection of citizens. Of great importance when creating an effective system of social protection is the division of the population into social groups for the importance of obtaining benefits and the opportunity to participate in socially useful activities.
The theoretical aspects of financial provision of social protection of the population
Keywords: соціальний захист; фінансове забезпечення; фонди фінансових ресурсів; фінанси соціального захисту; соціальні ризики; social security; financial support; financial resources; social security finances; social risks